ANALISIS FIGUR AMBU DALAM PROSESI MAPAG PANGANTN SUNDA - Nurzaini, Mayang Amalia (LP2M ISBI Bandung, 2023)
Mapag Pangantn is a bride and groom welcoming procession what be held at a Sundandese wedding party. The bride and the groom would welcomed with traditional music and dance performance. This procession appeared in the 1920s and continues to grow until now. The development includes various aspects, one of which is appeared of Ambus figure on Mapag Pangantn procession. Ambu is a Lngsrs wife who have humorous character. But in reality, representation of Ambus figure often contradict with the concept of Sundanese culture and norms in society. This research was conducted using a qualitative descriptive method with observation techniques and literature study.